2012
DOI: 10.1111/j.1600-0722.2011.00897.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of monomers in unstimulated whole saliva after treatment with resin‐based composite fillings in vivo

Abstract: Resin-based dental restorative materials contain allergenic methacrylate monomers, which may be released into saliva after restorative treatment. Monomers from resin-based composite materials have been demonstrated in saliva in vitro; however, studies analyzing saliva after restorative therapy are scarce. The aim of this study was to quantify methacrylate monomers in saliva after treatment with a resin-based composite filling material. Saliva was collected from 10 patients at four start points--before treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 46 publications
0
38
0
5
Order By: Relevance
“…Although numerous laboratory studies show release of resin monomers from dental materials (Van Landuyt et al, 2011), the extent to which they are released after restoration treatment in humans remains unclear. A recent saliva study in 10 adults found that treatment with a bisGMA-based filling led to increased bisGMA and other resin components in saliva shortly after treatment, but no detectable levels were found one week later (Michelsen et al, 2012). In a study of 20 children, urinary BPA levels increased after dental composite treatment and had not returned to baseline levels at the end of follow-up two weeks later (Martin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous laboratory studies show release of resin monomers from dental materials (Van Landuyt et al, 2011), the extent to which they are released after restoration treatment in humans remains unclear. A recent saliva study in 10 adults found that treatment with a bisGMA-based filling led to increased bisGMA and other resin components in saliva shortly after treatment, but no detectable levels were found one week later (Michelsen et al, 2012). In a study of 20 children, urinary BPA levels increased after dental composite treatment and had not returned to baseline levels at the end of follow-up two weeks later (Martin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…BPA became undetectable 1 and 24 h after the placement of the sealant [10,12]. It was concluded that due to the low level of BPA, there was no clinical risk after placement of fissure sealants, an assumption that was confirmed by other authors [10,13,14]. Indeed, considering the dose-response, the BPA level was too low to be toxic if the disease is linked to the amount of BPA released during dental treatment.…”
mentioning
confidence: 73%
“…However, the in vivo situation is not clear, some studies indicate initial short term exposure to monomers, either from short term leaching, or as contamination from the restorative treatment [26,28]. A low value of residual monomers in composite materials would minimize the risk of adverse reactions from dental monomers.…”
Section: Discussionmentioning
confidence: 96%
“…This indicates a greater potential for elution of monomers from TEC than for Z250. Previously, it has been reported larger amounts of residual monomer in the Tetric Ceram material, which was the precursor to TEC, than in Z250 [28].…”
Section: Discussionmentioning
confidence: 97%